Cultural Reversal: Why Does Obedience Lose With The Initiative - Slinták, Karel (International Journal of Entrepreneurial Knowledge, 2015)
The article deals with the question which management philosophy is better, management philosophy based on culture HOW or management philosophy based on culture WHY. With respect to this article, author used these techniques, namely quantitative research, case methodology and literature analysis. Consequently, from the research, it can be predicted that most companies prefer a management model which inclines more towards planning, organizing and controlling than to leadership. This approach is a part of the traditional management system through which the organizational culture of “HOW” is implemented. The hidden costs of this model are apathetic staff, lost revenues and mainly work-related stress. These factors, which cause a lack of participation in the workplace, similarly lead to paralysis of innovation capabilities of most companies. They negatively affect the overall productivity of the economy and cause considerable social costs. However, there is also alternative management system based on the WHY culture. This management system, which releases initiative, creativity and enthusiasm, was investigated in the Toyota, FAVI and W. L. Gore. Author found out that these companies are able to eliminate the negative consequences of the traditional management model. The key features of this model are trust, freedom and responsibility, all three of which enrich the system with the ability to learn iteratively from one’s own mistakes.